Rancang Bangun Sistem Pemantauan Cuaca Menggunakan Sensor Kecepatan Angin, Suhu dan Kelembaban Berbasis Internet of Things. - Alamsyah Alamsyah; Tan Suryani Sollu; I Komang Martawan; Kristanti Bongkaombo; Nurpadila (Jurusan Teknik Elektro Fakultas Teknik Universitas Halu Oleo, 2024)
Weather is information that is very necessary, especially on agricultural land, to support plant growth, productivity, and yield. Weather monitoring currently still uses a manual system, so it requires quite a lot of time and energy. Apart from that, manual monitoring also allows limited types of data that can be measured directly by humans. The weather monitoring system design is based on the parameters used, namely temperature, humidity, and wind speed, using the LoRa module, which can be accessed online and offline and in real-time on the website and LCD. The test results show that the system can work well with an average level of accuracy for each temperature, humidity, and wind speed sensor of 98.19%, 99.325%, and 98.17%, respectively.